2018
DOI: 10.20546/ijcmas.2018.708.308
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Management of Weeds in Maize (Zea mays L.)

Abstract: Weeds constituent one of the major economic important problem for maize growers and it can reduce yield up to 86 per cent. The magnitude of losses largely depends upon the composition of weed flora, period of crop-weed competition and its intensity. The highest weed control efficiency with lowest weed density and weed dry weight was noted in pre-emergence application of atrazine @ 1.0 kg a.i. ha -1 followed by (fb) one hand weeding (HW) at 30 DAS. K e y w o r d sWeed flora, Weed management practices, Weed dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…The application of broadleaf herbicide atrazine after 26 days of sowing (after 7 days of first irrigation), @ of 4.5 L ha -1 to all treatments against broadleaf weeds effectively controlled broadleaf weeds from 95% to 100% whereas, other species of grassy weeds were controlled from 40% to 50%, when they were at 3-4 leaves stage. Other scientists, who observed that the atrazine herbicide effectively controlled broadleaf weeds from 73% to 98%, obtained similar findings and poor to moderate efficacy against grassy weeds in corn (Idris et al, 2015;Rai et al, 2018). First cut of S. S. grass hybrid fodder was taken after 90 days of sowing during both the year's when 50% flowering was achieved.…”
Section: Resultsmentioning
confidence: 82%
“…The application of broadleaf herbicide atrazine after 26 days of sowing (after 7 days of first irrigation), @ of 4.5 L ha -1 to all treatments against broadleaf weeds effectively controlled broadleaf weeds from 95% to 100% whereas, other species of grassy weeds were controlled from 40% to 50%, when they were at 3-4 leaves stage. Other scientists, who observed that the atrazine herbicide effectively controlled broadleaf weeds from 73% to 98%, obtained similar findings and poor to moderate efficacy against grassy weeds in corn (Idris et al, 2015;Rai et al, 2018). First cut of S. S. grass hybrid fodder was taken after 90 days of sowing during both the year's when 50% flowering was achieved.…”
Section: Resultsmentioning
confidence: 82%
“…quence, adopting proper tillage practices including closer spacing and using suitable wheat varieties. Example atrazine @ 1.00 kg ha-1 + HW, 2 HW and paddy straw mulching, producing grain yield of (203.48 g, 188.34 g and 186.82 g) respectively, as compared to un-weeded plot (68.30 g) (Rai et al, 2018).…”
Section: S213mentioning
confidence: 99%
“…Jagung berkedudukan sebagai sumber karbohidrat sehingga merupakan komoditas yang mempunyai nilai strategis dan nilai ekonomis yang tinggi (Fitria et al, 2019). Jagung selain dimanfaatkan sebagai bahan pangan, juga dimanfaatkan sebagai bahan pakan (Rai et al, 2018) dan bahan baku industri (Karenga et al, 2022). Permintaan jagung di pasar Indonesia maupu di dunia terus meningkat seiring dengan meningkatnya jumlah penduduk dan industri yang menggunakannya sebagai bahan baku (Gawaksa et al, 2016).…”
Section: Pendahuluanunclassified